Counterpoint: The Insurance Institute for Highway Safety Study Actually Found Cities Using Red Light Cameras Had Higher Red Light Running Fatality Rates - Barbara Langland-Orban; Etienne E. Pracht; John T. Large (University of North Florida, 2012)
In February 2011, the Insurance Institute for Highway Safety (IIHS) disseminated their research study that compared red light running traffic fatality rates between cities that implemented red light camera (RLC) programs with cities that did not. The IIHS researchers concluded cities that used RLCs had a significantly larger percentage reduction in both red light running (RLR) fatality rates and total fatality rates at signalized intersections. Because a previous IIHS study on RLCs was found to use flawed research methods, as well as to incorrectly report findings, the current IIHS RLC analysis is reviewed for adherence to scientific methods. Our review reveals the 2011 IIHS study is logically flawed and violates basic scientific research methods that are required for a study's findings to be valid. It has neither internal nor external validity. More importantly, the IIHS did not fully explain the results of its analysis. Correctly interpreting its model's results actually shows that cities using RLCs had an estimated higher rate of red light running fatalities, specifically 25%, than cities that did not use RLCs in the period "after" cameras were used. Further, the IIHS study was only able to make statements suggesting favorable results from the use ofRLCs due to the biased selection ofsampled cities. The red light running fatality rate as well as the total fatality rate at all signalized intersections in cities that used cameras was higher in both the "before" and "after" time periods, which affirms that superior interventions exist. Also, we explain the IIHS' financial conflict ofinterest regarding photo enforcement.